2013
DOI: 10.5194/bg-10-3849-2013
|View full text |Cite
|
Sign up to set email alerts
|

Riparian zone control on base cation concentration in boreal streams

Abstract: Riparian zones (RZ) are a major factor controlling water chemistry in forest streams. Base cations' (BC) concentrations, fluxes, and cycling in the RZ merit attention because a changing climate and increased forest harvesting could have negative consequences, including re-acidification, for boreal surface waters. We present a two-year study of BC and silica (Si) flow-weighted concentrations from 13 RZ and 14 streams in different landscape elements of a boreal catchment in northern Sweden. The spatial variation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 75 publications
1
59
0
Order By: Relevance
“…The mineralogy is dominated by quartz (40 %), K-feldspar (25 %), plagioclase (23 %), amphibolites (7 %), muscovite (4 %) and chlorite (1 %; Ledesma et al, 2013). At ca.…”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mineralogy is dominated by quartz (40 %), K-feldspar (25 %), plagioclase (23 %), amphibolites (7 %), muscovite (4 %) and chlorite (1 %; Ledesma et al, 2013). At ca.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Fiebig et al, 1990;Hinton et al, 1998;Oquist et al, 2009;Lyon et al, 2011;Winterdahl et al, 2011;Grabs et al, 2012;Knorr, 2013;Leith, 2015;Ledesma et al, 2015). However, the special biogeochemical conditions of the riparian zone also have consequences for the transport of widely different substances such as nitrogen (Hill, 1996;Cirmo and McDonnell, 1997;Sabater et al, 2003), phosphorus (Mulholland, 1992), base cations (Ledesma et al, 2013), aluminium (Cory et al, 2007), mercury , persistent organic pollutants (Bergknut et al, 2011) and pesticides (Vidon et al, 2010). Furthermore, the riparian zone is gaining increasing recognition as an ecological hotspot (Jansson et al, 2007;Kuglerová et al, 2013;Nilsson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…2). A recent study by Ledesma et al (2013) has shown that the concept works well for other aspects of stream chemistry such as base cations. The model is driven by flow, stream chemistry, and soil temperature data.…”
Section: Dynamic Riparian Flow-concentration Integration Modelmentioning
confidence: 99%
“…The simple dynamic riparian flow-concentration integration model (RIM) is a hillslope scale model of riparian controls on stream [DOC] in forest catchments ). The concept behind the RIM development was based on the assumption that the riparian zone closest to the stream is a first-order factor controlling stream DOC (Winterdahl et al 2011a, b) and other streamwater chemistry in forest landscapes (Ledesma et al 2013). The RIM conceptualization was justified by the fact that the riparian zone is a biogeochemical hotspot where organic-rich soil consistently interacts with ground and surface waters (Grabs et al 2012) and thus riparian soil water [DOC] and flow paths effectively control stream [DOC].…”
Section: Introductionmentioning
confidence: 99%
“…(i) Stream water partly derives from wet peaty soils along the stream. Organic matter from the peaty zones may control the stream water base cation chemistry (Ledesma et al, 2013). These wet peaty soils could act as a cation exchanger that preferentially retains the heavy Mg isotope.…”
Section: Discussionmentioning
confidence: 99%